Phospholipase D regulates on-membrane diffusivity of a myristoylated protein and defines the PIP3 patch territory - Gen Honda; Chihuku Tanaka; Hidenori Hashimura; Tomoko Adachi; Mina Fujishiro; Nao Shimada; Satoshi Sawai; Miho Yanagisawa (Proceedings of the National Academy of Sciences, 2026)
In living cells, the control of molecular diffusion is pivotal for highly fluidic membranes to serve as substrates for biochemical reactions and cytoskeletal assemblies. Lateral diffusion in membranes depends on a highly diverse and homeostatically controlled lipid composition. This complexity has limited our understanding of how diffusivity in biological membranes is regulated. In this study, we show that lipid diffusion in model membranes decreases markedly in the presence of cytosolic extracts. The reduction in lipid diffusivity can be pharmacologically inhibited by targeting phospholipase D (PLD). Conversely, lipid diffusivity was reduced when PLD alone was added to the membrane. Phosphatidic acid (PA), a direct product of PLD, diffuses slowly, and its presence reduces the diffusivity of surrounding lipids. Furthermore, we found that PLD controls the lateral diffusion of a myristoylated protein PKBR1 in Dictyostelium cells, possibly through auxiliary electrostatic interactions between cationic residues located near the lipidated tail and anionic phospholipids. In line with the role of PKBR1 in regulating phosphatidylinositol(3,4,5)-trisphosphates (PIP3), PLD overexpression suppressed the size and lifetime of PIP3 microdomains as well as the sensitivity of GPCR-mediated PIP3 elevation. Our results underscore the importance of PLD and its product PA as regulators of lipidated protein diffusivity, facilitating the dynamical lateral organization of phosphoinositides in the plasma membrane.